A novel conditioning approach for amelioration of sludge dewaterability using activated carbon strengthening electrochemical oxidation and realized mechanism. (15th July 2022) - Dong, Yanting; Yuan, Haiping; Ge, Dongdong; Zhu, Nanwen
Highlights: A novel AC strengthening EC process was developed to improve sludge dewaterability. Moisture distribution was ameliorated beneficial for sludge dewatering. Morphological structure and rheological behaviors were optimized by EC/AC treatment. Highly hydrophilic organic matters were reduced increasing sludge hydrophobicity. Enhanced electron transfer capacity was responsible for strengthened EC oxidation. Abstract: Sludge dewatering is an essential process for reduction of sludge volume to decrease cost of ultimate disposal. In this study, a novel method using activated carbon (AC) strengthening electrochemical (EC) treatment (EC/AC) was adopted to improve greatly sludge dewaterability. It was shown that capillary suction time (CST) and water content of dewatered sludge cake (Wc) were reduced to 55.9 ± 1.24 s and 64.3 ± 1.23%, respectively, under the optimal conditions of EC voltage 20 V, EC time 30 min and 0.2 g/g dry solid (DS) AC. AC with rich functional groups as "the third electrode" intensified electrooxidation by forming multiple microelectrodes and electron transfer capacity and conductivity of sludge were strengthened by AC in EC system, which were illustrated by electrochemical analysis. It could be found that zeta potential and particle size were increased and surface roughness was reduced after EC/AC treatment intensifying sludge hydrophobicity. Form the results of rheological behaviors of sludge, flowability was strengthened and viscosity was weakened under the conditioning of EC/AC. Besides, colloidal force and gel-like network strength were lessened, which was also verified by organic matters and percentage of inviable cells. At the same time, intracellular matters were released and degraded and bound water was released converting into free water. In addition, sludge compressibility and structural strength were increased and porous structure was formed facilitating water outflow via addition of mesoporous AC as skeleton builder, which eventually led to an improved separation efficiency of solid-water and sludge dewaterability. The results of heavy metals suggested that sludge cake after EC/AC treatment was favorable for land application. Graphical abstract: Image, graphical abstract